Pendidikan Agama Islam sebagai Sarana Pembentukan Karakter dan Akhlak Mulia: (Study tentang implementasi nilai-nilai islam dalam kehidupan sehari-hari) - Najamudin Najamudin; Surahman Hidayat (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2024)
Islamic religious education plays an important role in the formation of character and noble morals. The main goal of Islamic religious education is to form children who are faithful, have good morals, and do good deeds. There are several means of Islamic religious education that can be used to form noble character and morals. Formal education such as madrasahs, religious schools, and Islamic universities can be effective means of Islamic religious education; Non-formal education such as pengajian, majlis taklim, and other religious activities can be flexible means of Islamic religious education; Informal education such as education in the family, community, and environment can be very effective means of Islamic religious education; Technology such as the internet, applications, and social media can be modern and effective means of Islamic religious education; Extracurricular Activities Extracurricular activities such as religious activities, social activities, and sports activities can be fun and effective means of Islamic religious education. In the formation of character and morals, Islamic religious education must pay attention to several aspects such as the formation of good and noble morals, such as honesty, patience, and caring. The formation of correct and consistent worship, such as prayer, fasting, and zakat. The formation of good and fair muamalah, such as being fair, honest, and caring. The formation of high and deep mukasyafah, such as understanding the essence of oneself, God, and the universe. The formation of good and noble character, such as being confident, independent, and responsible. Thus, Islamic religious education can form the character and morals of children who are good, noble, and pious.